From Page to Stage: Creating Original Theatre in Kuwait - Downs, Kathleen (2015)
Writer Craig Loomis, Assoc. Prof. of English at the American University of Kuwait, published a book in 2013 called The Salmiya Collection. In it, he described the diverse experiences of everyday life in a part of the world not clearly known or understood by outsiders: Salmiya, Kuwait. His tales chronicle ordinary Kuwaitis, expatriate professionals, local students, parents, and children as they struggle to make their way in a complex and changing world. The collection’s complex group of characters and situations resonated with me on a universal level, rather than just speaking to a specific time and place. I became convinced that the stories’ themes of change and transition, and the tensions they cause, would resonate with a larger audience in our ever-changing world. First, however, Dr. Loomis’ short stories had to be adapted to fit the theatrical structure of short plays. Writer Ken Downs, a former newspaper editor and current teacher, transformed the short stories into staged vignettes about daily life in the Middle East and, in particular, Salmiya, Kuwait. Several revisions later, the collection of short stories has emerged as nine one-act plays woven together as the fulllength play, Long Ago and not so Fay Away. Bringing this project together was not easy. Casting, rehearsals, rewrites, and weaving together both the pieces and the ensemble posed special challenges. This paper discusses how these challenges were overcome in our quest to create an original theatre experience about the Middle East—and life in general—that would be reflective without being alienating, and remain true to Dr. Loomis’ vision and voice